2011
DOI: 10.7577/formakademisk.128
|View full text |Cite
|
Sign up to set email alerts
|

When past and new experiences meet. Negotiating meaning with 3-D materials in early childhood education

Abstract: This article suggests that the process of meaning making is closely related to embodied experience and social interaction. The article is based on a study of specific contexts of visual arts education with 3–5 year old children. The study aims to enlarge understanding of relationships between children’s experience with three-dimensional (3-D) materials and their meaning-making processes. Empirical data were collected through observations of children’s play and video documentation of interactions between a prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
6
0
2
Order By: Relevance
“…It is a case of "interspecies pedagogy" in which we learnt from each other about issues relating to teaching and learning. What I learnt from Zvekki was surprisingly similar to what I learnt during my study of young children's (2-5 years) experiential learning (Fredriksen 2011a(Fredriksen , 2011b(Fredriksen , 2012(Fredriksen , 2016a(Fredriksen , 2017(Fredriksen , 2018. The embodied capacities for learning through experiences, which I discovered in co-research with children, were not only present in Zvekki, but sophisticated, vibrant and impossible to overlook (indeed dangerous to overlook).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…It is a case of "interspecies pedagogy" in which we learnt from each other about issues relating to teaching and learning. What I learnt from Zvekki was surprisingly similar to what I learnt during my study of young children's (2-5 years) experiential learning (Fredriksen 2011a(Fredriksen , 2011b(Fredriksen , 2012(Fredriksen , 2016a(Fredriksen , 2017(Fredriksen , 2018. The embodied capacities for learning through experiences, which I discovered in co-research with children, were not only present in Zvekki, but sophisticated, vibrant and impossible to overlook (indeed dangerous to overlook).…”
Section: Introductionsupporting
confidence: 61%
“…Horses' ability to sense moods, emotions and needs of others, which Blake (2007) calls "communication beyond senses" and "reading of thoughts", resembles Stern's (1998) A horse learns from emotional consequences of her/his behaviour (Wendt 2012), and, similarly to humans, "negotiates meanings" (learns) by connecting past and present experiences (Fredriksen 2011a;2011b). Horses are able to share experiences and learn from each other, for instance by observing and mimicking (De Georgio & De Georgio-Schoorl 2016).…”
Section: Cognitive Horsementioning
confidence: 99%
See 1 more Smart Citation
“…The radical intersubjectivity of the studentteacher relationship (Aspelin, 2010) is seen as entwined with the teaching style as well as the provoking materials. This also fits with the more general socio-cultural view of the importance of acquiring knowledge through dialogic interaction (Bruner, 1990), and through the continuous negotiation of meaning (Fredriksen, 2011) as speaking bodies and body-minds (Dewey, 1925). With reference to Merleau-Ponty (1994) and Shusterman (2008), Fredriksen asserts the role of the knowing body in these processes.…”
Section: Theoretical Approaches To the Inquiry Into Place Space And mentioning
confidence: 90%
“…My research found that the resistance of materials is especially important to a child's ability to negotiate meaning (Fredriksen, 2011a). If a child uses a material and experiences something that does not work as expected, this new insight can trigger the child's imaginative connection between their past and new experiences (Dewey, 2005(Dewey, [1934), motivate creative problem solving (Fredriksen, 2011b) and allow the child to leave a "personal signature" on the problem solution (Eisner, 2002). Examples involving Eva will show how she negotiated with materials and tools, and how she imagined problem solutions in her own personal ways.…”
mentioning
confidence: 99%